Hubungan Perilaku Hidup Bersih Dan Sehat (Phbs) Dengan Kejadian Diare Pada Balita Di Rs Mitra Husada Tangerang - Suminar, Mira; Saraswati, Dewa Ayu; Manurung, Betty Sortani Monika (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
ABSTRACT Background. The most common cause of death in children under five is diarrhea. The prevalence of diarrhea in children under five in Indonesia is 40.90%. From the results of data collection through the recapitulation of monthly diarrhea reports in Tangerang Regency, it is therefore necessary to increase family involvement by implementing PHBS. Objectives and benefits. This study aims to determine the relationship between clean and healthy living behavior with the incidence of diarrhea in toddlers. Research subject. 100 mothers who have children under five are hospitalized in the child care room and those who seek outpatient treatment are at the pediatrician at Mitra Husada Hospital, Tangerang. Based on the data, it was found that there was no relationship between PHBS and the incidence of diarrhea in toddlers with a P-value of 0.048, which means that there was a significant relationship between PHBS and the incidence of diarrhea. Based on the results of the analysis of the relationship between PHBS and the incidence of diarrhea, it was found that there were more than 48.3% of toddlers with family PHBS who experienced diarrhea. While good family PHBS is more in children under five, not diarrhea, which is 41.7%. The results of the statistical test based on the Chi-Square Test with a significance value of =0.05, where the results of the study were obtained, p=0.0001 which indicates >p or 0.05>0.0001. This shows that there is a relationship between PHBS and the incidence of diarrhea in toddlers at Mitra Husada Hospital Tangerang, the relationship between PHBS and the incidence of diarrhea in toddlers. The statistical test results show that the P Value is 0.048 less than (0.05) so that Ho fails to be rejected, meaning that there is a relationship between PHBS with diarrhea incidence at Mitra Husada Hospital Tangerang in 2022